PENERAPAN BEBAN JAMINAN AKAD MUDHARABAH DI PERBANKAN SYARIAH - Triyono, Muhyidin Muhammad Mukhtar Shidiq (Fakultas Hukum, Universitas Diponegoro, 2017)
In mudharabah contract practice in Indonesian syariah banking, the existence of imposition of guarantee on mudharabah agreement raises debate among scientists and Islamic scholars about the validity of mudharabahnya contract. This paper aims to determine the validity of mudharabah contracts in which there is a requirement for imposition of collateral. How to apply the imposition of guarantee on mudharabah contract in Indonesian syariah banking, and how the view of Islamic law and positive law regarding the imposition of guarantee on mudharabah contract in Indonesian sharia banking. There are interesting things in this paper because the imposition of Islamic banking in Indonesia actually uses the provisions of the Civil Code of mortgage and mortgage and the Law of Fiduciary Rights and Law which in fact is the legal arrangement of collateral for conventional banking (debt agreement receivable). The view of Islamic law regarding the imposition of guarantees on mudharabah contracts affects the invalidity of the mudharabah contract. The imposition of a guarantee on a mudharabah contract may convert a mudaraba transaction into a usury transaction prohibited in the Islamic Shari'a. This thus makes his mudharabah contract to be void and doubt its validity. Keywords : Assurance Charges, Akad Mudharabah, Syariah Banking, Indonesia